Validation of three prediction models for thrombosis recurrence in antiphospholipid syndrome patients based on a prospective cohort - Zhao, Yuan; Huang, Can; Qi, Wanting; Zhou, Yangzhong; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; Zeng, Xiaofeng (Rheumatic & musculoskeletal diseases open, 2023)
ObjectivesTo validate the performance of the adjusted global antiphospholipid syndrome (APS) score (aGAPSS), Padua score and Caprini score to predict thrombosis recurrence in APS.MethodsConsecutive thrombotic-APS patients were included. aGAPSS, Padua and Caprini score at baseline were collected. Harrell c-index and calibration curve were used to validate the prediction models.Results362 patients were enrolled. The mean age was 36.30±13.88 years old, and 209 (57.7%) were female. Patients were followed up for a median of 2.32 years, with 32 (8.84%) venous and 21 (5.80%) arterial thrombosis. The 1-year, 3-year and 5-year thrombosis risks were 5.0%, 14.3% and 17.9%, respectively. The Harrell c-indexes of aGAPSS, Padua and Caprini score were 0.54 (95% CI 0.44 to 0.64), 0.54 (95% CI 0.46 to 0.62), and 0.50 (95%CI 0.42 to 0.58), respectively. Padua score had the best discrimination to predict venous thrombosis (Harrell c-index=0.61, 95% CI 0.53 to 0.69). aGAPSS had the best discrimination to predict arterial thrombosis (Harrell c-index=0.61, 95% CI 0.47 to 0.75). The calibrations for predicting thrombosis within 1, 3 and 5 years of the three models were suboptimal.ConclusionThe performance of aGAPSS, Padua and Caprini score to predict thrombosis recurrence in APS were suboptimal. Arterial and venous thrombosis recurrence predictors were different. New prediction models are required for venous and arterial thrombosis separately.